Authenticity, cultural motivation and place attachment as antecedents to tourists’ recommend intention in Melaka and George Town heritage sites, Malaysia - Latiff, Khairunnisak (2019)
Melaka and George Town have been inscribed by the United Nations Educational, Scientific and Cultural Organization (UNESCO) as the World Cultural Heritage Sites. However, there are reports indicating that the authenticity of the cultural elements in these two heritage sites were questioned particularly by tourists. Therefore, this study attempts to address the issues by looking at dimensions of authenticity that draw tourists to both heritage sites and how these dimensions influence their place attachment and intention to recommend. By using the Stimulus-Organism-Response (S-O-R) model, this study proposes a conceptual framework with a total of 17 hypotheses to examine the relationship of i) authenticity and place attachment, ii) place attachment and intention to recommend, iii) authenticity and intention to recommend, iv) mediating role of attachment on authenticity and intention to recommend and v) moderating role of cultural motivation on authenticity and place attachment. Questionnaires were distributed to tourists who visited Melaka and George Town heritage sites through judgmental sampling. A total of 470 questionnaires filled by tourists were used in the analysis. SmartPLS was used to analyze the data. The findings revealed i) objective authenticity, constructive authenticity and existential authenticity have positive relationships with place attachment, ii) place attachment drives intention to recommend, iii) objective authenticity, existential authenticity, and food authenticity are significant stimuli of intention to recommend, iv) place attachment mediates the relationship between constructive authenticity and intention to recommend and the relationship between existential authenticity and intention to recommend and v) cultural motivation moderates the relationship between objective authenticity-place attachment, constructive authenticity-place attachment, and existential authenticity-place attachment. Drawing from the findings, this study discovered multiple dimensions of authenticity relevant to heritage sites, introduced attachment theory to understand the process in which authenticity impacts intention to recommend and extended the S-O-R model by introducing a moderating variable in understanding the strength of the relationship between authenticity and place attachment. Therefore, destination managers are suggested to emphasize on authenticity and attachment elements because these elements lead to tourists recommending and encouraging their friends and relatives to visit the heritage sites and therefore, indirectly promoting the heritage sites. However, this study did not examine tourists’ actual behavior and analyze place attachment at its sub-dimensional level. Therefore, it is recommended for future studies to examine these research gaps.